تشكیل اللّغة وبناء الحوار في النّص الدرامي - بومالي, حنان (Université de M'sila, 2016)
إن الـنص الـدرامي بوصـفه مجموعـة مـن العناصـر تسـهم فـي تشـكیل الصـورة الدرامیـة، مـن خـلال الحیویة والتفاعل الحي بین هذه العناصر التي تعطي الشمول والرسوخ والهیمنة للصورة، والمسرحیة عمل درامـي مـأخوذ مـن الحیـاة بـروح فنیـة یحتـوي علـى حكایـة طویلـة أو قصـیرة، مترابطـة الأجـزاء یقـوم بهـا أشخاص لهم سمات اجتماعیة ونفسیة خاصة تتناسب مع طبیعة الحكي، وتعتمد علـى لغـة الحـوار أكثـر من السرد في جمیع مراحل تطورها. وتسهم هذه العناصر الدرامیة في طبیعة التأثیر المراد بلوغه ودرجته المختلفـة وصـولا إلـى القـیم المتعـددة جمالیـة وعاطفیـة وفنیـة، ویقـع علـى عـاتق المؤلـف الانتبـاه إلـى هـذه العناصـــر وإعطائهــا الأهمیــة اللازمــة مــن لغــة وفكـــرة وحـــوار وجـــو نفســـي عـــام وشخصـــیات وغیرهـــا، وإن اختلف طابع التشدید وغلبة بعض العناصر لكل لون درامي منها مثلما یختلـف المؤلفـون فیمـا بیـنهم في التشدید على بعض العناصر دون الأخرى وإعطائها الأولویة. Summary The dramatic text as a set of elements that contribute to the formation of the dramatic image, through dynamic, live interaction between these elements, which gives comprehensive and well-established and hegemony, and theatrical dramatic action taken from the life in the spirit of the art contains the tale is long or short, threaded by persons with social and psychological attributes particularly suit the nature of storytelling, and depend on the language of dialogue over the narrative in all stages of development. The dramatic elements in the nature of the effect to be achieved and the different degree of access to multiple values, emotional and artistic beauty, rests with the author drew attention to these items and give them the necessary importance of language and the idea of dialogue and atmosphere itself in other figures, albeit nature and prevalence of some elements of each color as ones vary dramatically among the authors emphasize some elements without the other and giving it priority
Keywords: dramatic text-image-interaction-theatr-الـنص الـدرامي-الصـورة-المسرحیة